Pengaruh Keuangan Daerah terhadap Tingkat Kemiskinan di Aceh - Rico Ricardo; Ayu Muchlisah; Feriansyah (Jurnal Informatika Ekonomi Bisnis, 2023)
Poverty is one of the problems faced by Indonesia from the past until now. Various ways have been done to overcome the problem of poverty. One of the efforts that have been made by the Government of Indonesia is to issue a regional autonomy policy. The existence of this policy gives authority to local governments to regulate their own regions. This policy is given to all provinces in Indonesia, including Aceh. Aceh is the province with the highest poverty rate on the island of Sumatra, although it has a higher original regional income (PAD) than the province with the lowest poverty rate on the island of Sumatra. Aceh also has a greater natural resources revenue-sharing fund (DBH SDA) than the province of West Sumatra. In addition, Aceh also received special autonomy funds (DOK), which were only given to the provinces of Aceh, Papua, and West Papua. This study aims to analyze the effect of PAD, DBH SDA and DOK on the poverty rate of Aceh Province for the 2008-2020 period. This research uses panel data regression involving 23 districts/cities of Aceh Province. The results of the study show that only local real revenue has a significant and negative effect on poverty levels.